2021
DOI: 10.1111/hir.12396
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 information seeking needs and behaviour among citizens in Isfahan, Iran: A qualitative study

Abstract: Background Access to reliable and credible health information improves individuals’ personal care level in crises, such as the coronavirus disease 2019 (COVID‐19) pandemic. It subsequently results in enhancing the community's health and reducing the health system's costs. Objectives This study aimed to investigate the COVID‐19 related information seeking behaviour demonstrated by citizens in Isfahan, Iran. Methods This research was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…However, during the Ebola pandemic in Liberia in 2018, a study found that community trust in non-governmental organizations (NGOs) was stronger than in government [30]. People seek information from various resources to update their knowledge and become more prepared in the face of COVID-19 [31]. Our result showed that 62.3% of the rural communities needed additional information about COVID-19.…”
Section: Discussionmentioning
confidence: 76%
“…However, during the Ebola pandemic in Liberia in 2018, a study found that community trust in non-governmental organizations (NGOs) was stronger than in government [30]. People seek information from various resources to update their knowledge and become more prepared in the face of COVID-19 [31]. Our result showed that 62.3% of the rural communities needed additional information about COVID-19.…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, the Medical Library Association describes health information-seeking behavior as the capacity to know the significance of well-being data, methods of obtaining wellbeing data, and how to apply that information in daily life ( Eriksson-Backa et al, 2012 ; Soleymani et al, 2021 ). Li et al (2016) also address how individuals seek well-being data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A large amount of literature has already been published and numerous researches are still going on to study the exact nature of the virus as it has started mutating. [ 12 13 ] As this is a new virus to the already existing coronavirus family, lots of assumptions regarding disease progression and management have been made. Considering this, various studies have been conducted assessing the role of medical status and systemic diseases in disease severity.…”
Section: Discussionmentioning
confidence: 99%